2007
DOI: 10.1177/000313480707301104
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Management of Intussusception in Adults: A New Paradigm in the Computed Tomography Era

Abstract: Intussusception has been considered an operative indication in adults as a result of the risk of ischemia and the possibility of a malignant lead point. Computed tomographic (CT) scans can reveal unsuspected intussusception. All CT reports from July 1999 to December 2005 were scanned electronically for letter strings to include the keyword intussusception. Identified CT scans were analyzed to characterize the intussusception and associated findings. Clinical, laboratory, pathological, and follow-up variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 46 publications
1
53
1
6
Order By: Relevance
“…30 As such, retrospective studies have demonstrated successful nonoperative management in as many as 82% of radiographic intussusceptions, even in the setting of gastrointestinal symptoms. 31,32 This has created some degree of controversy regarding optimal management of these patients.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…30 As such, retrospective studies have demonstrated successful nonoperative management in as many as 82% of radiographic intussusceptions, even in the setting of gastrointestinal symptoms. 31,32 This has created some degree of controversy regarding optimal management of these patients.…”
Section: Treatmentmentioning
confidence: 99%
“…In the large majority of entero-enteric intussusceptions without lead point mass and short affected segments-defined as less than 3.5 to 3.8 cm in several series-expectant management can be employed with serial clinical and imaging evaluations where necessary to ensure resolution. [31][32][33] When indicated, surgery may be performed laparoscopically or open, depending on the skill and experience of the surgeon. Regardless of the approach, the intussusception must be successfully identified and then carefully reduced (in children) or resected (adults).…”
Section: Treatmentmentioning
confidence: 99%
“…Among the surgical options, transanal resection (transanal endoscopic microsurgery) using a posterior presacral approach (anterior tumours) or mucosectomy, and abdominal surgery for large tumours, are preferred. This type of benign tumour has the potential to become malignant; the only treament option that has been proven to be effective is surgery involving complete excision of the lesion, which results in normalization of electrolyte levels and prevents progression to a malignant tumour (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Many reviews support invagination as an indication for surgery in adults due to the risk of intestinal ischemia and possible malignancy of the lead point of invagination. However, we consider it important to take associated symptoms into account and on the basis of these conduct more accurate diagnostic studies to rule out a tumor origin if not done previously; moreover, the diameter and length of the invagination, together with the presence or absence of an associated lesion, and the type of invagination are predictors of spontaneous resolution (13,14).…”
Section: Discussionmentioning
confidence: 99%